Respiratory infections in pregnancy and early life—association with the development of islet autoimmunity and type 1 diabetes in children: systematic review and meta-analysis of observational studiesResearch in context - Claire J. Sung; Orlaith M. Plowman; Anna J. Maxwell; William D. Rawlinson; Maria E. Craig; Ki Wook Kim (EClinicalMedicine, 2025)
Summary: Background: Respiratory tract infections (RTIs) in pregnancy and early childhood are potential environmental triggers of islet autoimmunity (IA) and type 1 diabetes (TD). We reviewed the association between gestational and childhood RTIs and the development of IA or T1D in the offspring. Methods: Systematic review and meta-analysis, analysed using random effects models, of observational human studies from Medline and EMBASE, without language restriction, from inception until Jan 6, 2025. The inclusion criteria were cohort, case-control, nested case control or retrospective cohort studies investigating confirmed RTI in childhood or pregnancy by reported history or detection by throat swab before/at IA seroconversion and/or T1D diagnosis in children aged < 18 years. The study is registered with PROSPERO, CRD42020193860. Findings: The systematic review included 26 studies of childhood RTIs involving 12,236,305 participants (14,646 cases, 12,221,659 controls) and four studies of gestational RTIs involving 109,976 participants (979 cases, 108,997 controls). Study design and quality varied, with moderate to high statistical heterogeneity. Meta-analysis of 15 studies demonstrated that childhood RTIs were significantly associated T1D (OR 1.47, 95% CI 1.23–1.75, p < 0.0001) but not significantly associated with IA. Meta-analysis of studies investigating gestational RTIs and T1D found no significant associations and only one of the studies found an association between maternal RTIs in the first trimester based on history and T1D in the offspring (OR 2.31, 95% CI 1.32–4.04, p = 0.002). Interpretation: Our analysis suggests childhood RTIs were significantly associated with risk of T1D, highlighting the need to further investigate the association between childhood RTIs using molecular testing and subsequent risk of IA/T1D. Funding: JDRF, NHMRC.